Monitoring the Process and Characterizing Symptoms of Suckling Mouse Inoculation Promote Isolating Viruses from Ticks - Tang, Shuang; Hu, Sijing; Xiao, Jian; Zhang, Yanfang; Su, Zhengyuan; Wu, Qiaoli; Yang, Juan; Liu, Xijia; Zhang, Zhong; Zhu, Qiong; Shi, Junming; Moming, Abilimiti; et al. (Zoonoses (Burlington, Mass.), 2023)
Suckling mouse inoculation is an important method that has been used for years to isolate viruses from ticks; however, this method has usually been briefly described in the literature on a case-by-case basis upon successful isolation rather than providing extensive details. This study describes the procedure from preparation of tick homogenates to identification of virus isolation using the suckling mouse inoculation method. The transient and persistent features were characterized and the incidence of manifestations that developed in the suckling mice, especially in mice from which viruses were isolated, is reported. We identified 22 symptoms that developed in mice, including 13 transient symptoms that recovered by the end of the observation period and 7 persistent symptoms that the mice suffered from throughout the observation period. Persistent symptoms (lateral positioning and dead) and transient symptoms (malaise, emaciation, and difficulty turning over) were the main symptoms based on the high overall incidence. Moreover, we showed that mice from which viruses were isolated had a concentrated period and advanced days of disease onset. This study provides detailed information necessary for better use of suckling mouse inoculation to isolate viruses from ticks, which may benefit optimization of this method to identify, discover, and acquire tick-borne viruses.